CHO‘LPON SHE’RIYATIDAGI AYRIM PERIFRAZALARNING LINGVOPOETIK XUSUSIYATLARI - Tòxtayeva Zaynura Òktam qizi (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2024)
This thesis discusses the linguopoetic features of Cho„`lpon's work, which is considered one of the major branches of modern literature, and some of the periphrases used in it. The paraphrases reflected by Cholpon were reflected based on the characteristics of the language of the period, and its linguopoetic qualities were the main goal of our thesis.